Effect of erythropoietin loading chitosan-tripolyphosphate nanoparticles on an IgA nephropathy rat model - ZHANG, XIAOLI (D.A. Spandidos, 2014)
The aim of the present study was to investigate the effect of erythropoietin (EPO) loading chitosan-tripolyphosphate (CS-TPP) nanoparticles on an immunoglobulin A nephropathy (IgAN) rat model. CS-TPP nanoparticles were produced from CS and TPP and EPO was loaded by mixing with the nanoparticles. The IgAN rat models were randomly divided into three groups: the CS-TPP-EPO group, CS-TPP group and EPO group. Hemoglobin (Hb), blood urea nitrogen (BUN) and creatinine (Cr) levels were measured in each group using a Biochemical Analyzer (Hitachi, Tokyo, Japan). The average size of nanoparticles was 485±12 nm and the encapsulation efficiency of EPO was 78.45%. The EPO release curve in CS-TPP-EPO nanoparticles exhibited a biphasic distribution in vitro. The levels of BUN and Cr in the CS-TPP-EPO group were significantly lower compared with the control group (P<0.05); however, the level of Hb in the CS-TPP-EPO group was higher compared with the other groups (P<0.05). The changes in Hb, BUN and Cr in the CS-TPP-EPO group were maintained for less than one week following the end of the treatment with CS-TPP-EPO nanoparticles. In conclusion, the CS-TPP-EPO nanoparticles had a lower toxicity compared with EPO and CS-TPP treatment. Furthermore, CS-TPP-EPO may improve the therapeutic effect in the IgAN model. This suggests that CS-TPP-EPO nanoparticles may be a potential therapeutic drug for the treatment of patients with IgAN.